PENINGKATAN KUALITAS PENDIDIKAN MELALUI PROFESIONALISME GURU DAN IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH - Syafrizal Syafrizal (Jurusan Geografi Fakultas Ilmu Sosial Universitas Negeri Padang, 2015)
Abstrak To improve the educational quality is an importan attemp that should be done by all Indonesian and government. The bundles of educational problems have to be solved and distributed not only to the municipal government but also to the prefectural government and the stakeholders of education. The distribution of task and responbility on the improvement of educational quality cannot be done automatically without stakeholders’ comprehension and understanding of the importance of educational improvement. But, teachers and school principal at least can do much when the stakeholdersgive much attention and prosperity to make them better life and more professional. In addition, the concept of school based management should be implemented soon to support the decentralization of educational management. It hopefully could make more effective beurocracy. However, it has to be implement wisely and carefully to avoid wider corruption, collusion, and nepotism at the local and root level.